FORMATION OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE OF CHEMISTRY AND AGROCHEMISTRY STUDENTS IN A MULTILINGUAL EDUCATIONAL ENVIRONMENT - Kaipbergenova, Feruza Tulepbergenovna (SCIENCE and SOCIETY, 2026)
This article examines the development of foreign language oral communicative competence in higher education for students majoring in chemistry. It explores the importance of foreign languages as a professional tool for the scientific, academic, and international activities of future specialists. Particular attention is paid to the educational environment in the Republic of Karakalpakstan, characterized by a multilingual environment and growing labor market demands
Keywords: foreign language communicative competence; chemistry students; professionally oriented learning; multilingual education; higher education